PENGEMBANGAN MEDIA PEMBELAJARAN KREATIF BERBASIS ANIMASI POWTOON DI SEKOLAH DASAR - Ratih Widya Kumala Sari; Feny Rita Fiantika; Prayogo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research adopts the ADDIE model in its development, with special attention given to design aspects, validation processes, and product testing, involving 28 students pursuing education in class IV-B at SDN Tembok Dukuh III Surabaya as participants. The researchers collected diverse information that contributed to the development process of learning aids and their effectiveness evaluation. Research findings indicate that the learning aid integrating Powtoon animation has successfully met validity and appropriateness standards, while demonstrating positive impacts on learning enthusiasm and students' comprehension levels regarding geometric shape concepts. The integration of ethnomathematics through the Powtoon animation platform has proven to be an effective solution in delivering mathematical content to fourth-grade elementary school students. This study proposes recommendations to enhance learning quality by adopting interactive learning media to deepen students' understanding of geometric shape concepts.